Saudi Vision 2030: Nation Branding Arab Saudi menjadi Esports Hub Internasional - Muhammad Rizky Eko Putra; Ario Bimo Utomo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Saudi Arabia's Vision 2030 marks a profound strategic shift towards economic diversification, with the esports sector identified as a key growth driver. This study analyzes Saudi Arabia's ambition to become an international esports hub through the lens of Simon Anholt's Competitive Identity theory, encompassing six dimensions: Tourism, Export Brands, Policy, Investment, Culture, and People. Utilizing relevant data, the research demonstrates how Vision 2030 initiatives systematically align with each dimension, shaping Saudi Arabia's global image as a modern, innovative, and dynamic nation. The analysis reveals a coordinated and massively funded approach to building a sustainable esports ecosystem, attracting investment, developing local talent, and projecting a new national identity. While challenges related to perception and sustainability persist, findings suggest that Saudi Arabia's esports strategy is an integral component of a broader nation branding effort, aiming to enhance its global influence and competitiveness on the world stage.